The Pandemic, Cash and Retail Payment Behaviour: Insights from the Future of Payments Database - Raphael Auer; Giulio Cornelli; Jon Frost (Center for Economic Studies and ifo Institute (CESifo), 2023)
The Covid-19 pandemic has been a shock to retail payment behaviour. How have the changes differed across countries? What do they imply for the future of cash and digital payments? We assemble a new "Future of Payments" database on retail payment behaviour for up to 95 countries over September 2019 to June 2022. We compare this with measures of the severity of the Covid-19 pandemic, using variation in the timing of waves of cases, changes in mobility and lockdown measures across countries. We find that card-not-present payments, payment app downloads and the volume of cash in circulation all rose in weeks of more stringent lockdowns. Changes were less pronounced in countries with higher mobile penetration. However, recent data suggest that some effects reversed once lockdowns were eased, and mobility rebounded.
Keywords: E42; I18; O32; O33; 330; retail payments; cash; Covid-19 pandemic; digital innovation